Whole life costs and project procurement in port, coastal and fluvial engineering how to escape the cost boxes - Simm, Jonathan (Thomas Telford, 2003)
This guide provides the necessary advice and date to break down the barriers between cost boxes so that costs can be considered holistically. This leads to more informed project decisions and can reduce costs over the life of an asset.
Keywords: River engineering -- Economic aspects.; Coastal engineering -- Economic aspects.; Life cycle costing.; Harbors -- Design and construction -- Economic aspects.; elektronické knihy; electronic books